Sample Solution

\(2\:cos\:\theta \:sin\:\phi =sin\:\left(\theta +\phi \right)-sin\:\left(\theta -\phi \right)\)
untitled-document-16-9cbde385-ad0a-4c74-864f-362c1a2d74cc

Question:-01

  1. State whether the following statements are true or false. Justify with a short proof or a counter example.
a) The space l 3 l 3 l^(3)l^3l3 is a Hilbert space
Answer:

Statement: The space l 3 l 3 l^(3)l^3l3 is a Hilbert space.

Justification:

A Hilbert space is a complete inner product space. That is, it is a vector space equipped with an inner product that is complete in the metric induced by the inner product.
The space l 3 l 3 l^(3)l^3l3 consists of all sequences ( x 1 , x 2 , x 3 , ) ( x 1 , x 2 , x 3 , ) (x_(1),x_(2),x_(3),dots)(x_1, x_2, x_3, \ldots)(x1,x2,x3,) such that n = 1 | x n | 3 < n = 1 | x n | 3 < sum_(n=1)^(oo)|x_(n)|^(3) < oo\sum_{n=1}^{\infty} |x_n|^3 < \inftyn=1|xn|3<.
  1. Inner Product: We can define an inner product on l 3 l 3 l^(3)l^3l3 as follows:
x , y = n = 1 x n y n ¯ x , y = n = 1 x n y n ¯ (:x,y:)=sum_(n=1)^(oo)x_(n) bar(y_(n))\langle x, y \rangle = \sum_{n=1}^{\infty} x_n \overline{y_n}x,y=n=1xnyn¯
This definition satisfies the properties of an inner product (conjugate symmetry, linearity, and positive-definiteness).
  1. Completeness: The space l 3 l 3 l^(3)l^3l3 is not complete with respect to this inner product. To see this, consider the sequence of sequences x ( k ) = ( 1 , 1 2 , , 1 k , 0 , 0 , ) x ( k ) = ( 1 , 1 2 , , 1 k , 0 , 0 , ) x^((k))=(1,(1)/(2),dots,(1)/(k),0,0,dots)x^{(k)} = (1, \frac{1}{2}, \ldots, \frac{1}{k}, 0, 0, \ldots)x(k)=(1,12,,1k,0,0,). Each x ( k ) x ( k ) x^((k))x^{(k)}x(k) is in l 3 l 3 l^(3)l^3l3, but its limit as k k k rarr ook \to \inftyk, which is the sequence ( 1 , 1 2 , 1 3 , ) ( 1 , 1 2 , 1 3 , ) (1,(1)/(2),(1)/(3),dots)(1, \frac{1}{2}, \frac{1}{3}, \ldots)(1,12,13,), is not in l 3 l 3 l^(3)l^3l3 because n = 1 ( 1 n ) 3 = n = 1 1 n 3 = sum_(n=1)^(oo)((1)/(n))^(3)=oo\sum_{n=1}^{\infty} \left(\frac{1}{n}\right)^3 = \inftyn=1(1n)3=.
Therefore, l 3 l 3 l^(3)l^3l3 is not a Hilbert space because it is not complete with respect to the inner product.

Page Break
b) Any non zero bounded linear functional on a Banach space is an open map.
Answer:

Statement: Any non-zero bounded linear functional on a Banach space is an open map.

Justification:

A map T : X Y T : X Y T:X rarr YT: X \to YT:XY between topological spaces is said to be open if the image of every open set in X X XXX under T T TTT is open in Y Y YYY.
Let X X XXX be a Banach space and f : X R f : X R f:X rarrRf: X \to \mathbb{R}f:XR (or C C C\mathbb{C}C) be a non-zero bounded linear functional. We want to show that f f fff is an open map.
  1. Boundedness: Since f f fff is bounded, there exists a constant C > 0 C > 0 C > 0C > 0C>0 such that | f ( x ) | C x | f ( x ) | C x |f(x)| <= C||x|||f(x)| \leq C \|x\||f(x)|Cx for all x X x X x in Xx \in XxX.
  2. Non-Zero: f f fff is non-zero, which means there exists some x 0 X x 0 X x_(0)in Xx_0 \in Xx0X such that f ( x 0 ) 0 f ( x 0 ) 0 f(x_(0))!=0f(x_0) \neq 0f(x0)0.
  3. Open Map: Consider an open ball B ( x , ϵ ) B ( x , ϵ ) B(x,epsilon)B(x, \epsilon)B(x,ϵ) in X X XXX centered at x x xxx with radius ϵ > 0 ϵ > 0 epsilon > 0\epsilon > 0ϵ>0. We want to show that f ( B ( x , ϵ ) ) f ( B ( x , ϵ ) ) f(B(x,epsilon))f(B(x, \epsilon))f(B(x,ϵ)) is an open set in R R R\mathbb{R}R (or C C C\mathbb{C}C).
    • Take y f ( B ( x , ϵ ) ) y f ( B ( x , ϵ ) ) y in f(B(x,epsilon))y \in f(B(x, \epsilon))yf(B(x,ϵ)). Then there exists z B ( x , ϵ ) z B ( x , ϵ ) z in B(x,epsilon)z \in B(x, \epsilon)zB(x,ϵ) such that f ( z ) = y f ( z ) = y f(z)=yf(z) = yf(z)=y.
    • Since z B ( x , ϵ ) z B ( x , ϵ ) z in B(x,epsilon)z \in B(x, \epsilon)zB(x,ϵ), we have z x < ϵ z x < ϵ ||z-x|| < epsilon\|z – x\| < \epsilonzx<ϵ.
    • Using linearity and boundedness of f f fff, we get | f ( z ) f ( x ) | C z x < C ϵ | f ( z ) f ( x ) | C z x < C ϵ |f(z)-f(x)| <= C||z-x|| < C epsilon|f(z) – f(x)| \leq C \|z – x\| < C \epsilon|f(z)f(x)|Czx<Cϵ.
    • This means y = f ( z ) y = f ( z ) y=f(z)y = f(z)y=f(z) lies in an open interval ( f ( x ) C ϵ , f ( x ) + C ϵ ) ( f ( x ) C ϵ , f ( x ) + C ϵ ) (f(x)-C epsilon,f(x)+C epsilon)(f(x) – C \epsilon, f(x) + C \epsilon)(f(x)Cϵ,f(x)+Cϵ) which is contained in f ( B ( x , ϵ ) ) f ( B ( x , ϵ ) ) f(B(x,epsilon))f(B(x, \epsilon))f(B(x,ϵ)).
Thus, f ( B ( x , ϵ ) ) f ( B ( x , ϵ ) ) f(B(x,epsilon))f(B(x, \epsilon))f(B(x,ϵ)) contains an open interval around every point y y yyy in it, making f ( B ( x , ϵ ) ) f ( B ( x , ϵ ) ) f(B(x,epsilon))f(B(x, \epsilon))f(B(x,ϵ)) an open set. Therefore, f f fff is an open map.
In conclusion, the statement “Any non-zero bounded linear functional on a Banach space is an open map” is true, and we have justified it with a short proof.

Page Break
c) Every bounded linear map on a complex Banach space has an eigen value.
Answer:

Statement: Every bounded linear map on a complex Banach space has an eigenvalue.

Justification:

The statement is false.
An eigenvalue λ λ lambda\lambdaλ for a bounded linear map T : X X T : X X T:X rarr XT: X \to XT:XX on a complex Banach space X X XXX is a complex number such that there exists a non-zero vector x X x X x in Xx \in XxX satisfying T ( x ) = λ x T ( x ) = λ x T(x)=lambda xT(x) = \lambda xT(x)=λx.

Counterexample:

Consider the right shift operator T : 2 2 T : 2 2 T:ℓ^(2)rarrℓ^(2)T: \ell^2 \to \ell^2T:22 on the complex Banach space 2 2 ℓ^(2)\ell^22 of square-summable sequences. The operator T T TTT is defined as follows:
T ( ( x 1 , x 2 , x 3 , ) ) = ( 0 , x 1 , x 2 , x 3 , ) T ( ( x 1 , x 2 , x 3 , ) ) = ( 0 , x 1 , x 2 , x 3 , ) T((x_(1),x_(2),x_(3),dots))=(0,x_(1),x_(2),x_(3),dots)T((x_1, x_2, x_3, \ldots)) = (0, x_1, x_2, x_3, \ldots)T((x1,x2,x3,))=(0,x1,x2,x3,)
Let’s assume, for the sake of contradiction, that T T TTT has an eigenvalue λ λ lambda\lambdaλ and corresponding eigenvector x = ( x 1 , x 2 , x 3 , ) x = ( x 1 , x 2 , x 3 , ) x=(x_(1),x_(2),x_(3),dots)x = (x_1, x_2, x_3, \ldots)x=(x1,x2,x3,) such that T ( x ) = λ x T ( x ) = λ x T(x)=lambda xT(x) = \lambda xT(x)=λx.
Then, we have:
( 0 , x 1 , x 2 , x 3 , ) = λ ( x 1 , x 2 , x 3 , ) ( 0 , x 1 , x 2 , x 3 , ) = λ ( x 1 , x 2 , x 3 , ) (0,x_(1),x_(2),x_(3),dots)=lambda(x_(1),x_(2),x_(3),dots)(0, x_1, x_2, x_3, \ldots) = \lambda (x_1, x_2, x_3, \ldots)(0,x1,x2,x3,)=λ(x1,x2,x3,)
This implies 0 = λ x 1 0 = λ x 1 0=lambdax_(1)0 = \lambda x_10=λx1, x 1 = λ x 2 x 1 = λ x 2 x_(1)=lambdax_(2)x_1 = \lambda x_2x1=λx2, x 2 = λ x 3 x 2 = λ x 3 x_(2)=lambdax_(3)x_2 = \lambda x_3x2=λx3, and so on. Since x x xxx is assumed to be a non-zero eigenvector, x 1 0 x 1 0 x_(1)!=0x_1 \neq 0x10, which implies λ = 0 λ = 0 lambda=0\lambda = 0λ=0. But this contradicts the fact that x 1 = λ x 2 x 1 = λ x 2 x_(1)=lambdax_(2)x_1 = \lambda x_2x1=λx2 because x 1 x 1 x_(1)x_1x1 cannot be zero.
Therefore, the right shift operator T T TTT on 2 2 ℓ^(2)\ell^22 does not have an eigenvalue, disproving the statement.

Page Break
d) The image of a Cauchy sequence under a bounded linear map is also a Cauchy sequence.
Answer:

Statement: The image of a Cauchy sequence under a bounded linear map is also a Cauchy sequence.

Justification:

The statement is true.
Let ( x n ) ( x n ) (x_(n))(x_n)(xn) be a Cauchy sequence in a normed space X X XXX, and let T : X Y T : X Y T:X rarr YT: X \to YT:XY be a bounded linear map into another normed space Y Y YYY. We want to show that ( T ( x n ) ) ( T ( x n ) ) (T(x_(n)))(T(x_n))(T(xn)) is a Cauchy sequence in Y Y YYY.

Proof:

  1. Bounded Linear Map: Since T T TTT is bounded, there exists a constant M > 0 M > 0 M > 0M > 0M>0 such that T ( x ) M x T ( x ) M x ||T(x)|| <= M||x||\| T(x) \| \leq M \| x \|T(x)Mx for all x X x X x in Xx \in XxX.
  2. Cauchy Sequence: Given any ϵ > 0 ϵ > 0 epsilon > 0\epsilon > 0ϵ>0, there exists N N NNN such that for all m , n N m , n N m,n >= Nm, n \geq Nm,nN, x m x n < ϵ M x m x n < ϵ M ||x_(m)-x_(n)|| < (epsilon )/(M)\| x_m – x_n \| < \frac{\epsilon}{M}xmxn<ϵM.
  3. Image under T T TTT: We have
    T ( x m ) T ( x n ) = T ( x m x n ) T ( x m ) T ( x n ) = T ( x m x n ) ||T(x_(m))-T(x_(n))||=||T(x_(m)-x_(n))||\| T(x_m) – T(x_n) \| = \| T(x_m – x_n) \|T(xm)T(xn)=T(xmxn)
    Using the boundedness of T T TTT,
    T ( x m ) T ( x n ) M x m x n < M ϵ M = ϵ T ( x m ) T ( x n ) M x m x n < M ϵ M = ϵ ||T(x_(m))-T(x_(n))|| <= M||x_(m)-x_(n)|| < M(epsilon )/(M)=epsilon\| T(x_m) – T(x_n) \| \leq M \| x_m – x_n \| < M \frac{\epsilon}{M} = \epsilonT(xm)T(xn)Mxmxn<MϵM=ϵ
    for all m , n N m , n N m,n >= Nm, n \geq Nm,nN.
Therefore, ( T ( x n ) ) ( T ( x n ) ) (T(x_(n)))(T(x_n))(T(xn)) is a Cauchy sequence in Y Y YYY, proving the statement.

Page Break
e) If A A A\mathrm{A}A is a bounded linear operator on a Hilbert space such that A A = I A A = I AA^(**)=I\mathrm{AA}^*=\mathrm{I}AA=I, then A A = I A A = I A^(**)A=I\mathrm{A}^* \mathrm{~A}=\mathrm{I}A A=I.
Answer:

Statement: If A A A\mathrm{A}A is a bounded linear operator on a Hilbert space such that A A = I A A = I AA^(**)=I\mathrm{AA^*} = \mathrm{I}AA=I, then A A = I A A = I A^(**)A=I\mathrm{A^*A} = \mathrm{I}AA=I.

Justification:

The statement is true.

Proof:

  1. Given Condition: We are given that A A A\mathrm{A}A is a bounded linear operator on a Hilbert space H H HHH and A A = I A A = I AA^(**)=I\mathrm{AA^*} = \mathrm{I}AA=I.
  2. Identity Operator: I I I\mathrm{I}I is the identity operator on H H HHH.
  3. To Prove: We need to show that A A = I A A = I A^(**)A=I\mathrm{A^*A} = \mathrm{I}AA=I.
  4. Step 1: Take any x H x H x in Hx \in HxH and consider A x A x A^(**)x\mathrm{A^*}xAx. We have
    A ( A x ) = ( A A ) x = I x = x A ( A x ) = ( A A ) x = I x = x A(A^(**)x)=(AA^(**))x=Ix=x\mathrm{A} (\mathrm{A^*} x) = (\mathrm{AA^*}) x = \mathrm{I} x = xA(Ax)=(AA)x=Ix=x
    This shows that A x A x A^(**)x\mathrm{A^*} xAx is in the range of A A A\mathrm{A}A.
  5. Step 2: Now consider A ( A x ) A ( A x ) A^(**)(Ax)\mathrm{A^*} (\mathrm{A} x)A(Ax). We have
    A ( A x ) = ( A A ) x A ( A x ) = ( A A ) x A^(**)(Ax)=(A^(**)A)x\mathrm{A^*} (\mathrm{A} x) = (\mathrm{A^* A}) xA(Ax)=(AA)x
    Since A x A x A^(**)x\mathrm{A^*} xAx is in the range of A A A\mathrm{A}A, we can write A ( A x ) = x A ( A x ) = x A^(**)(Ax)=x\mathrm{A^*} (\mathrm{A} x) = xA(Ax)=x.
  6. Step 3: Combining Steps 1 and 2, we get
    A ( A x ) = x ( A A ) x = x ( A A I ) x = 0 A ( A x ) = x ( A A ) x = x ( A A I ) x = 0 A^(**)(Ax)=xLongrightarrow(A^(**)A)x=xLongrightarrow(A^(**)A-I)x=0\mathrm{A^*} (\mathrm{A} x) = x \implies (\mathrm{A^* A}) x = x \implies (\mathrm{A^* A} – \mathrm{I}) x = 0A(Ax)=x(AA)x=x(AAI)x=0
    for all x H x H x in Hx \in HxH.
  7. Step 4: Since ( A A I ) x = 0 ( A A I ) x = 0 (A^(**)A-I)x=0(\mathrm{A^* A} – \mathrm{I}) x = 0(AAI)x=0 for all x H x H x in Hx \in HxH, it follows that A A = I A A = I A^(**)A=I\mathrm{A^* A} = \mathrm{I}AA=I.
Therefore, the statement is true.

Page Break

Question:-02

  1. a) Characterise all bounded linear functionals on a Hilbert space.
Answer:
In functional analysis, a bounded linear functional on a Hilbert space H H H\mathcal{H}H is a linear functional f : H C f : H C f:HrarrCf: \mathcal{H} \to \mathbb{C}f:HC (or R R R\mathbb{R}R for real Hilbert spaces) that satisfies the boundedness condition:
f = sup x = 1 | f ( x ) | < f = sup x = 1 | f ( x ) | < ||f||=s u p_(||x||=1)|f(x)| < oo\| f \| = \sup_{\| x \| = 1} |f(x)| < \inftyf=supx=1|f(x)|<
Here, ||*||\| \cdot \| denotes the norm on H H H\mathcal{H}H.

Riesz Representation Theorem

The Riesz Representation Theorem provides a complete characterization of bounded linear functionals on a Hilbert space. The theorem states that for every bounded linear functional f f fff on a Hilbert space H H H\mathcal{H}H, there exists a unique vector y H y H y inHy \in \mathcal{H}yH such that for all x H x H x inHx \in \mathcal{H}xH:
f ( x ) = x , y f ( x ) = x , y f(x)=(:x,y:)f(x) = \langle x, y \ranglef(x)=x,y
Here, , , (:*,*:)\langle \cdot, \cdot \rangle, is the inner product on H H H\mathcal{H}H.

Properties

  1. Linearity: f ( a x + b y ) = a f ( x ) + b f ( y ) f ( a x + b y ) = a f ( x ) + b f ( y ) f(ax+by)=af(x)+bf(y)f(ax + by) = a f(x) + b f(y)f(ax+by)=af(x)+bf(y) for all x , y H x , y H x,y inHx, y \in \mathcal{H}x,yH and a , b C a , b C a,b inCa, b \in \mathbb{C}a,bC (or R R R\mathbb{R}R).
  2. Boundedness: f < f < ||f|| < oo\| f \| < \inftyf<.
  3. Uniqueness: The vector y y yyy in the Riesz representation is unique.
  4. Norm Preservation: f = y f = y ||f||=||y||\| f \| = \| y \|f=y, where y y yyy is the vector in the Riesz representation.
  5. Continuity: Bounded linear functionals are continuous.
  6. Dual Space: The set of all bounded linear functionals on H H H\mathcal{H}H forms the dual space H H H^(**)\mathcal{H}^*H.

Examples

  1. Finite-Dimensional Spaces: In finite-dimensional Hilbert spaces, every linear functional is bounded.
  2. Sequence Spaces: In 2 2 ℓ^(2)\ell^22, the space of square-summable sequences, the bounded linear functional corresponding to a sequence ( a n ) ( a n ) (a_(n))(a_n)(an) is f ( x ) = n = 1 a n x n f ( x ) = n = 1 a n x n f(x)=sum_(n=1)^(oo)a_(n)x_(n)f(x) = \sum_{n=1}^{\infty} a_n x_nf(x)=n=1anxn.
  3. Function Spaces: In L 2 ( [ 0 , 1 ] ) L 2 ( [ 0 , 1 ] ) L^(2)([0,1])L^2([0, 1])L2([0,1]), the space of square-integrable functions on [ 0 , 1 ] [ 0 , 1 ] [0,1][0, 1][0,1], the bounded linear functional corresponding to a function g ( x ) g ( x ) g(x)g(x)g(x) is f ( f ) = 0 1 f ( x ) g ( x ) d x f ( f ) = 0 1 f ( x ) g ( x ) d x f(f)=int_(0)^(1)f(x)g(x)dxf(f) = \int_{0}^{1} f(x) g(x) \, dxf(f)=01f(x)g(x)dx.
The Riesz Representation Theorem provides a powerful tool for understanding bounded linear functionals on Hilbert spaces, essentially identifying them with elements of the Hilbert space itself.

Page Break
b) Show that the map T : R 3 R 2 T : R 3 R 2 T:R^(3)rarrR^(2)\mathrm{T}: \mathbf{R}^3 \rightarrow \mathbf{R}^2T:R3R2 given by T ( x 1 , x 2 , x 3 ) = ( x 1 + x 2 , x 3 ) T x 1 , x 2 , x 3 = x 1 + x 2 , x 3 T(x_(1),x_(2),x_(3))=(x_(1)+x_(2),x_(3))\mathrm{T}\left(\mathrm{x}_1, \mathrm{x}_2, \mathrm{x}_3\right)=\left(\mathrm{x}_1+\mathrm{x}_2, \mathrm{x}_3\right)T(x1,x2,x3)=(x1+x2,x3) is an open map.
Answer:
To show that the map T : R 3 R 2 T : R 3 R 2 T:R^(3)rarrR^(2)\mathrm{T}: \mathbf{R}^3 \rightarrow \mathbf{R}^2T:R3R2 given by T ( x 1 , x 2 , x 3 ) = ( x 1 + x 2 , x 3 ) T x 1 , x 2 , x 3 = x 1 + x 2 , x 3 T(x_(1),x_(2),x_(3))=(x_(1)+x_(2),x_(3))\mathrm{T}\left(\mathrm{x}_1, \mathrm{x}_2, \mathrm{x}_3\right)=\left(\mathrm{x}_1+\mathrm{x}_2, \mathrm{x}_3\right)T(x1,x2,x3)=(x1+x2,x3) is an open map, we need to show that the image of any open set in R 3 R 3 R^(3)\mathbf{R}^3R3 under T T T\mathrm{T}T is also an open set in R 2 R 2 R^(2)\mathbf{R}^2R2.

Step 1: Take an Arbitrary Open Set in R 3 R 3 R^(3)\mathbf{R}^3R3

Let U U UUU be an arbitrary open set in R 3 R 3 R^(3)\mathbf{R}^3R3. Take an arbitrary point y y y\mathbf{y}y in T ( U ) T ( U ) T(U)\mathrm{T}(U)T(U). We need to show that there exists an open ball in R 2 R 2 R^(2)\mathbf{R}^2R2 centered at y y y\mathbf{y}y that is entirely contained in T ( U ) T ( U ) T(U)\mathrm{T}(U)T(U).

Step 2: Pre-image of y y y\mathbf{y}y

Since y y y\mathbf{y}y is in T ( U ) T ( U ) T(U)\mathrm{T}(U)T(U), there exists x = ( x 1 , x 2 , x 3 ) x = ( x 1 , x 2 , x 3 ) x=(x_(1),x_(2),x_(3))\mathbf{x} = (x_1, x_2, x_3)x=(x1,x2,x3) in U U UUU such that T ( x ) = y T ( x ) = y T(x)=y\mathrm{T}(\mathbf{x}) = \mathbf{y}T(x)=y.

Step 3: Open Ball Around x x x\mathbf{x}x

Because U U UUU is open in R 3 R 3 R^(3)\mathbf{R}^3R3, there exists an open ball B ϵ ( x ) B ϵ ( x ) B_(epsilon)(x)B_{\epsilon}(\mathbf{x})Bϵ(x) centered at x x x\mathbf{x}x with radius ϵ > 0 ϵ > 0 epsilon > 0\epsilon > 0ϵ>0 such that B ϵ ( x ) U B ϵ ( x ) U B_(epsilon)(x)sube UB_{\epsilon}(\mathbf{x}) \subseteq UBϵ(x)U.

Step 4: Image of the Open Ball

Consider the image T ( B ϵ ( x ) ) T ( B ϵ ( x ) ) T(B_(epsilon)(x))\mathrm{T}(B_{\epsilon}(\mathbf{x}))T(Bϵ(x)). We claim that this set contains an open ball in R 2 R 2 R^(2)\mathbf{R}^2R2 centered at y y y\mathbf{y}y.

Step 5: Show the Open Ball in R 2 R 2 R^(2)\mathbf{R}^2R2

Take any point z = ( z 1 , z 2 ) z = ( z 1 , z 2 ) z=(z_(1),z_(2))\mathbf{z} = (z_1, z_2)z=(z1,z2) in R 2 R 2 R^(2)\mathbf{R}^2R2 such that z y < ϵ z y < ϵ ||z-y|| < epsilon\|\mathbf{z} – \mathbf{y}\| < \epsilonzy<ϵ. We need to show that z z z\mathbf{z}z is in T ( B ϵ ( x ) ) T ( B ϵ ( x ) ) T(B_(epsilon)(x))\mathrm{T}(B_{\epsilon}(\mathbf{x}))T(Bϵ(x)).
We can write z y = ( z 1 y 1 , z 2 y 2 ) z y = ( z 1 y 1 , z 2 y 2 ) z-y=(z_(1)-y_(1),z_(2)-y_(2))\mathbf{z} – \mathbf{y} = (z_1 – y_1, z_2 – y_2)zy=(z1y1,z2y2). Since z y < ϵ z y < ϵ ||z-y|| < epsilon\|\mathbf{z} – \mathbf{y}\| < \epsilonzy<ϵ, we have:
| z 1 y 1 | < ϵ and | z 2 y 2 | < ϵ | z 1 y 1 | < ϵ and | z 2 y 2 | < ϵ |z_(1)-y_(1)| < epsilonquad”and”quad|z_(2)-y_(2)| < epsilon|z_1 – y_1| < \epsilon \quad \text{and} \quad |z_2 – y_2| < \epsilon|z1y1|<ϵand|z2y2|<ϵ
Now, consider the point x = ( x 1 + z 1 y 1 , x 2 z 1 + y 1 , x 3 + z 2 y 2 ) x = ( x 1 + z 1 y 1 , x 2 z 1 + y 1 , x 3 + z 2 y 2 ) x^(‘)=(x_(1)+z_(1)-y_(1),x_(2)-z_(1)+y_(1),x_(3)+z_(2)-y_(2))\mathbf{x}’ = (x_1 + z_1 – y_1, x_2 – z_1 + y_1, x_3 + z_2 – y_2)x=(x1+z1y1,x2z1+y1,x3+z2y2). Clearly, x x < ϵ x x < ϵ ||x^(‘)-x|| < epsilon\|\mathbf{x}’ – \mathbf{x}\| < \epsilonxx<ϵ, so x x x^(‘)\mathbf{x}’x is in B ϵ ( x ) B ϵ ( x ) B_(epsilon)(x)B_{\epsilon}(\mathbf{x})Bϵ(x) and hence in U U UUU.
We have:
T ( x ) = ( x 1 + z 1 y 1 + x 2 z 1 + y 1 , x 3 + z 2 y 2 ) = ( z 1 , z 2 ) = z T ( x ) = ( x 1 + z 1 y 1 + x 2 z 1 + y 1 , x 3 + z 2 y 2 ) = ( z 1 , z 2 ) = z T(x^(‘))=(x_(1)+z_(1)-y_(1)+x_(2)-z_(1)+y_(1),x_(3)+z_(2)-y_(2))=(z_(1),z_(2))=z\mathrm{T}(\mathbf{x}’) = (x_1 + z_1 – y_1 + x_2 – z_1 + y_1, x_3 + z_2 – y_2) = (z_1, z_2) = \mathbf{z}T(x)=(x1+z1y1+x2z1+y1,x3+z2y2)=(z1,z2)=z
Thus, z z z\mathbf{z}z is in T ( B ϵ ( x ) ) T ( B ϵ ( x ) ) T(B_(epsilon)(x))\mathrm{T}(B_{\epsilon}(\mathbf{x}))T(Bϵ(x)), and we conclude that T ( B ϵ ( x ) ) T ( B ϵ ( x ) ) T(B_(epsilon)(x))\mathrm{T}(B_{\epsilon}(\mathbf{x}))T(Bϵ(x)) contains an open ball in R 2 R 2 R^(2)\mathbf{R}^2R2 centered at y y y\mathbf{y}y.

Conclusion

Since y y y\mathbf{y}y was arbitrary, we have shown that T ( U ) T ( U ) T(U)\mathrm{T}(U)T(U) is open in R 2 R 2 R^(2)\mathbf{R}^2R2. Therefore, T T T\mathrm{T}T is an open map.

Page Break
c) Check whether a finite dimensional normed linear space is reflexive? Justify your answer.
Answer:
In functional analysis, a Banach space X X XXX is said to be reflexive if the natural embedding J : X X J : X X J:X rarrX^(****)J: X \to X^{**}J:XX, which maps each x X x X x in Xx \in XxX to its evaluation functional J ( x ) J ( x ) J(x)J(x)J(x) in the bidual X X X^(****)X^{**}X, is an isometric isomorphism. In other words, X X XXX is reflexive if it is isometrically isomorphic to its bidual X X X^(****)X^{**}X.

Finite-Dimensional Case

In a finite-dimensional normed linear space X X XXX, the dual space X X X^(**)X^*X is also finite-dimensional, and it has the same dimension as X X XXX. Furthermore, the bidual X X X^(****)X^{**}X will also be finite-dimensional and have the same dimension as X X XXX and X X X^(**)X^*X.

Isomorphism Between X X XXX and X X X^(****)X^{**}X

In finite dimensions, every linear map that is injective is also surjective. Therefore, the natural embedding J : X X J : X X J:X rarrX^(****)J: X \to X^{**}J:XX is not only injective but also surjective, making it a linear isomorphism.

Isometry

The natural embedding J J JJJ is also an isometry, meaning it preserves the norm. This is true in any normed space, not just finite-dimensional ones.

Conclusion

Combining these facts, we can conclude that in a finite-dimensional normed linear space X X XXX, the natural embedding J : X X J : X X J:X rarrX^(****)J: X \to X^{**}J:XX is an isometric isomorphism. Therefore, every finite-dimensional normed linear space is reflexive.

Page Break
\(a^2=b^2+c^2-2bc\:Cos\left(A\right)\)
Scroll to Top
Scroll to Top